Nonlinear dynamics : materials, theory and experiments : selected lectures, 3rd Dynamics Days South America, Valparaiso 3-7 November 2014 /: materials, theory and experiments : selected lectures, 3rd Dynamics Days South America, Valparaiso 3-7 November 2014. ([2016]) - Unknown
No abstract available